The Bro1-domain-containing protein Myopic/HDPTP coordinates with Rab4 to regulate cell adhesion and migration. - Chen, D.Y.; Li, M.Y.; Wu, S.Y.; Lin, Y.L.; Tsai, S.P.; Lai, P.L.; Lin, Y.T.; Kuo, J.C.; Meng, T.C.; Chen, G.C. (Journal of Cell Science, 2012)
Protein tyrosine phosphatases (PTPs) are a group of tightly regulated enzymes that coordinate with protein tyrosine kinases to control protein phosphorylation during various cellular processes. Using genetic analysis in Drosophila non-transmembrane PTPs, we identified one role that Myopic (Mop), the Drosophila homolog of the human His domain phosphotyrosine phosphatase (HDPTP), plays in cell adhesion. Depletion of Mop results in aberrant integrin distribution and border cell dissociation during Drosophila oogenesis. Interestingly, Mop phosphatase activity is not required for its role in maintaining border cell cluster integrity. We further identified Rab4 GTPase as a Mop interactor in a yeast two-hybrid screen. Expression of the Rab4 dominant-negative mutant leads to border cell dissociation and suppression of Mop-induced wing-blade adhesion defects, suggesting a critical role of Rab4 in Mop-mediated signaling. In mammals, it has been shown that Rab4-dependent recycling of integrins is necessary for cell adhesion and migration. We found that human HDPTP regulates the spatial distribution of Rab4 and integrin trafficking. Depletion of HDPTP resulted in actin reorganization and increased cell motility. Together, our findings suggest an evolutionarily conserved function of HDPTP-Rab4 in the regulation of endocytic trafficking, cell adhesion and migration.